A novel ratiometric fluorescent probe for selective detection of bisulfite in living cells. Issue 5 (12th January 2017) - Chen, Zhen; Chen, Fengzao; Sun, Yuanchao; Liu, Heng; He, Hanping; Zhang, Xiuhua; Wang, Shengfu
Abstract : In this work, a new type of ratiometric fluorescent probe APCT for bisulfite anion based on Michael-type addition reaction was designed. Abstract : A new type of ratiometric fluorescent probe, 8-(diethylamino)-2-methyl-4-oxo-4 H -pyrano[2, 3- b ]chromen-10-ylium tetrafluoroborate (APCT), is reported. A new type of ratiometric fluorescent probe, 8-(diethylamino)-2-methyl-4-oxo-4 H -pyrano[2, 3- b ]chromen-10-ylium tetrafluoroborate (APCT), is reported. This probe can successfully detect bisulfite anions with a detection limit of 6.1 × 10 −7 M based on Michael-type addition reaction in pH = 7.4 Tris buffer solution containing 70% DMSO (v/v). The response time of the probe is approximately 5 min. Upon treating with bisulfite anions, the probe exhibits an obvious blue shift from 560 nm to 510 nm and the fluorescence intensity ratio at 510 nm and 560 nm ( I 510 / I 560 ) displays a good linear relationship with the concentration of HSO3 − in the range of 20–120 μM. Additionally, the preliminary cell imaging experiments using HeLa cells demonstrate that the probe can be used to detect intracellular bisulfite anions.